Indonesia Fair : Upaya Diplomasi Ekonomi dalam Membuka Gerbang Kerjasama Manufaktur Kereta Api Indonesia-Bangladesh - Rosyidi, M. Habib; Ali, Yusril Ihza; ., Djatmiko; Joisangadji, Alvansyah (Global and Policy Journal of International Relations, 2020)
Indonesia under the administration Joko Widodo 2015-2019 is very concerned about the economic sector which realized in Indonesian economic diplomacy. These diplomacy is directed at the national interest, economic growth, and people’s welfare. In 2018, Indonesia has held the Indonesia Fair in Bangladesh in order to strengthen cooperation partners between Indonesia and Bangladesh. This event has opened trade cooperation between Indonesia and Bangladesh. This event is in form of business meetings and trade expo followed by companies from Indonesia. These program opened trade cooperation in the railway manufacturing industry sector. Bilateral relations that have existed for a long time are important factors in enhancing the economic advance of Indonesia. Therefore, this paper will further discuss the Indonesian economic diplomacy through Indonesia Fair 2018 in Bangladesh, what are the reasons for Indonesia to held this event, and how is the perspective of Bangladesh in deciding to cooperate with Indonesia in the field of railway manufacturing after Indonesia Fair 2018.Keywords: Economic Diplomacy, Indonesia Fair 2018, Railway Manufacture Industry, BangladeshIndonesia di bawah pemerintahan Presiden Joko Widodo 2015-2019 sangat konsen pada sektor ekonomi yang diwujudkan dengan gencarnya diplomasi ekonomi Indonesia. Diplomasi ini diarahkan untuk kepentingan nasional, pertumbuhan ekonomi, dan kesejahteraan rakyat Indonesia. Pada tahun 2018, Indonesia mengadakan Indonesia Fair di Bangladesh dalam rangka penguatan mitra kerjasama antara Indonesia dan Bangladesh. Kegiatan ini berupa temu bisnis dan pameran dagang yang diikuti oleh perusahaan dari Indonesia. Kegiatan ini telah membuka kerjasama dagang di sektor industri manufaktur perkeretaapian. Hubungan bilateral yang terjalin sejak lama merupakan faktor penting dalam meningkatkan kemajuan ekonomi Indonesia. Oleh sebab itu, paper ini akan lebih dalam mengulas tentang diplomasi ekonomi Indonesia melalui Indonesia Fair 2018 di Bangladesh, apa saja yang menjadi konsiderasi Indonesia dalam menyelenggarakan kegiatan ini serta bagaimana sudut pandang Bangladesh dalam memutuskan untuk bekerjasama dengan Indonesia di bidang manufaktur perkeretaapian pasca Indonesia Fair 2018.Kata Kunci: Diplomasi Ekonomi, Indonesia Fair 2018, Industri Manufaktur Kereta Api, Bangladesh DOI : https://doi.org/10.33005/jgp.v8i01.2172